Nano Drug Delivery System with Resveratrol as Promising Novel Adjuvant Therapy for Diabetic Non-Healing Wounds: A Literature Review - Sari, Ni Wayan Puspita; Els, Vanessa; Indrayani, Agung Wiwiek (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Diabetes mellitus (DM) is a metabolic disease characterized by increased blood sugar levels (hyperglycemia) and is associated with impaired function of β cells. The uncontrolled and prolonged hyperglycemia in DM can cause complications. One of the most common is diabetic non-healing wounds, the leading cause of disability in people with diabetes, therefore adjuvant therapy is needed. Compounds from natural ingredients are currently getting the spotlight in recent studies conducted to prove their effect on non-healing wounds, such as Resveratrol (RSV). This review aims to discuss the potential of RSV as a novel adjuvant therapy and its delivery system strategy in the case of diabetic non-healing wounds. We conducted an extensive search from three online scientific databases such as ScienceDirect, ResearchGate, and PubMed on February-March 2023. Keywords used are